Studies on hydration mechanism of composite cement based mortars through microstructure investigation - Karadumpa, Chandra Sekhar; Pancharathi, Rathish Kumar (Journal of Structural Engineering, 2024)
The manufacturing process of cement involves combustion of fossil fuels and calcination of limestone, resulting in emission of CO₂ into the atmosphere. In recent years, blended cements with partial replacement of mineral additives have drawn significant attention with their ability to conserve the available natural resources and also to reduce the effect of global warming produced by greenhouse gases. Composite Cement (CC) is a cement involved with maximum utilization of industrial wastes such as Fly Ash (FA) and Granulated Blast Furnace Slag (GBFS) in Ordinary Portland Cement (OPC) to develop low carbon binder and promoting the sustainable construction practice. In the present study, the share of OPC, FA and GBFS is optimized at 50%, 20% and 30% respectively by interblending these constituents in accordance with the IS 16415:2015 specifications. CC being a newly developed ternary blended cement, before putting this into construction practice, it is important to study the behaviour of CC in development of hydrates of cement which are responsible for the strength and performance of any concrete. The present study mainly focuses on the manifestation of phase changes involved in hydrates of cement with progressive curing and the same is studied using SEM, EDX, BSE, XRF and FT-IR techniques. The mechanical behaviour of CC mortars is compared with reference OPC mortars by correlating with microstructure analysis.